233k views
2 votes
1/9 (2m - 16) = 1/3 (2m + 4)

2 Answers

3 votes

Answer:

m = -7

Explanation:

1. Multiply both sides of the equation by 9 to eliminate the fractions.

1/9 (2m - 16) = 1/3 (2m + 4)

*9 *9

2m - 16 = 3 (2m + 4)

2. Then you're going to distribute the 3 on the right side of the equation.

2m - 16 = 6m + 12

3. Rearrange the terms.

2m - 16 = 6m + 12

+16 +16

2m = 6m +28

-6m -6m

-4m = 28

4. Divide both sides by -4.

-4m = 28

/-4 /-4

m = -7

m = -7 is your final answer. Hope this helped :)

User Andere
by
5.6k points
2 votes
-7 hopefully hope it helps
User Thomas Murphy
by
5.2k points